2019
DOI: 10.1038/s41398-019-0541-3
|View full text |Cite
|
Sign up to set email alerts
|

Major depression and enhanced molecular senescence abnormalities in young and middle-aged adults

Abstract: Recent evidence suggests a significant overlap in biological changes between major depression and aging across the lifespan. We aim to evaluate the impact of a major depressive episode on the S enescence- A ssociated S ecretory P henotype (SASP) index, a dynamic secretory molecular pattern indicative of cellular senescence. We also tested the potential moderators of the association between major depression and the SASP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 65 publications
4
33
0
Order By: Relevance
“…Several potential biological mechanisms have been proposed in linking immunological changes to affective neurobiology. MDD has been associated with immune cell senescence in particular, and a study by Diniz et al found that a senescence associated secretory phenotype was associated with MDD severity ( Diniz et al, 2019 ). Future research could examine the relationships between a broader range of inflammatory markers (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Several potential biological mechanisms have been proposed in linking immunological changes to affective neurobiology. MDD has been associated with immune cell senescence in particular, and a study by Diniz et al found that a senescence associated secretory phenotype was associated with MDD severity ( Diniz et al, 2019 ). Future research could examine the relationships between a broader range of inflammatory markers (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Although significant, the effect was relatively subtle, comparable to that identified in CpG methylation data. Diniz et al (2019) found MDD exhibited greater molecular senescence in young and middle-aged adults by examining the impact of MDD on the senescence associated secretory phenotype (SASP), a dynamic secretory molecular pathway indicative of cellular senescence 4 . More severe episodes of depression present with higher SASP indices and a significant interaction between current MDD episode and overweight, thus comorbid current MDD plus being overweight had the highest SASP index.…”
Section: Discussionmentioning
confidence: 99%
“…Immune cell senescence has a well-documented effect on both epigenome and transcriptome 3 . MDD has also been linked to the senescence associated secretory phenotype (SASP), a dynamic secretory molecular pathway indicative of cellular senescence 4 . This speaks to a more elaborate biology linking cell biology, transcriptome and inflammatory proteins produced by the cell.…”
Section: Introductionmentioning
confidence: 99%